Case series of rectovaginal fistula: clinical analysis and management strategies - Fatima, Ayesha; Blair, Elaine; Gamage, Upul Ranchagada; Iqbal, Aleem; Jamjute, Pradumna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Rectovaginal fistula (RVF) is a rare but serious obstetric complication with significant physical and emotional consequences. This retrospective review analyzed three cases of RVF that occurred between June 2023 and June 2024 to identify clinical patterns and propose improvements in management. All cases involved primigravid women who experienced either prolonged second-stage labor or rapid expulsive efforts; instrumental deliveries and episiotomies were performed in two instances. Primary repairs utilized vicryl and vicryl rapide sutures; however, two patients developed persistent fistulae necessitating colorectal referral and further surgical intervention, including temporary stoma formation. Delayed diagnosis and inconsistent post-operative care were identified as key issues. The findings highlight the importance of comprehensive perineal assessment, standardized repair techniques, and early multidisciplinary involvement. To prevent and manage RVF more effectively, the study recommends enhanced clinician training, updated local guidelines, and structured postnatal follow-up for early detection of complications.